2023
DOI: 10.1007/s00432-023-04960-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of GP-2250 on cultured virus-negative Merkel cell carcinoma cells: preliminary results

Abstract: Background Even in the novel immunotherapy era, Merkel cell carcinoma (MCC) remains challenging in its treatment. Apart from Merkel cell polyomavirus (MCPyV) associated MCC, this cancer is linked in about 20% of cases to ultraviolet-induced mutational burden frequently causing aberrations in Notch and PI3K/AKT/mTOR signalling pathways. The recently developed agent GP-2250 is capable to inhibit growth of cells of different cancers, including pancreatic neuroendocrine tumors. The objective of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Other therapeutic approaches currently focus on the energy metabolism, such as glycolysis and enhanced glucose uptake, as well as decreased oxidative metabolism. Energy metabolism is altered in many cancers and may be addressed with the use of antisense oligonucleotides or GAPDH-inhibitors such as fumaric acid esters [33,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Other therapeutic approaches currently focus on the energy metabolism, such as glycolysis and enhanced glucose uptake, as well as decreased oxidative metabolism. Energy metabolism is altered in many cancers and may be addressed with the use of antisense oligonucleotides or GAPDH-inhibitors such as fumaric acid esters [33,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…GP-2250 (Figure 1) is a relatively novel anti-neoplastic substance that has recently been investigated in different cancers [13][14][15][16]. The substance is an oxathiazinane (tetrahydro-1,4,5-oxathiazin-4,4-dioxide) and has inhibitory effects on glyceraldehyde 3-phosphate dehydrogenase (GAPDH) expression and activity, selectively resulting in oxidative stress, mitochondrial dysfunction, and programmed cell death in cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in in vitro as well as in vivo experiments, GP-2250 is able to downregulate the viability of pancreatic carcinoma cells, which is also accompanied by the induction of apoptosis as well as necrosis. The same study group reported on the anti-tumor activity of GP-2250, investigating other malignancies as well [13][14][15][16]. Importantly, the substance proved to be safe in nude mice, indicated by acute or chronic toxicity only at extremely high concentrations (acute toxicity at 2000 mg/kg*BW and chronic toxicity at concentrations higher than 1000 mg/kg*BW in nude mice).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation